The effectiveness of a nationwide universal coverage campaign of insecticide-treated bed nets on childhood malaria in Malawi - Collins O. F. Zamawe; Kanan Nakamura; Akira Shibanuma; Masamine Jimba (Malaria Journal, 2016)
Abstract Background Although the universal coverage campaign of insecticide-treated mosquito bed nets (ITNs) has been associated with improved malaria outcomes, recent reports indicate that the campaign is losing its sparkle in some countries. In Malawi, the universal coverage campaign was implemented in 2012, but its impacts are yet to be ascertained. Thus, this study examined the effects of the campaign on malaria morbidity among children in Malawi. Methods This is a repeated cross-sectional study. The study used nationally-representative malaria indicator survey (MIS) data collected in 2012 and 2014. In total, the analysis included 4193 children between the ages of 6 and 59 months (2171 from 2012 MIS and 2022 from 2014 MIS). ITNs coverage and malaria morbidity before (2012 = pre-test/control) and after (2014 = post-test/treated) the universal coverage campaign of ITNs were compared. The treated and control samples were matched on measured relevant covariates using propensity scores. Results The mean number of ITNs per household improved significantly from 1.1 (SD 1.0) in 2012 to 1.4 (SD 1.1) in 2014 (p < 0.001). Nonetheless, the prevalence of malaria among children increased considerably from 27.7 % (2012) to 32.0 % (2014) (p = 0.002). The risk of malaria was also significantly higher in 2014 compared to 2012 (RR = 1.14; 95 % CI 1.01–1.29). Besides, the use of bed nets was not significantly associated with malaria morbidity in 2014 (RR = 0.92; 95 % CI 0.76–1.12), but it was in 2012 (RR = 0.83; 95 % CI 0.70–1.00). Conclusions The universal coverage campaign of ITNs was not associated with a reduced burden of malaria among children in Malawi. This was likely due to increased insecticide resistance, inconsistent use of bed nets and under-utilization of other methods of malaria control. This calls for a multifaceted approach in the fight against malaria instead of simple dependence on ITNs. In particular, local or community level malaria interventions should go hand in hand with the universal coverage campaign.